Kajian Hukum Pelaksanaan Vaksinasi Covid-19 di Indonesia Ditinjau dari Perspektif Hak Asasi Manusia - Muhamat Agung Sanjaya; Dewi Asri Puannandini; Ida Kurniasih (JURNAL PEMULIAAN HUKUM, 2021)
Implementation of the Covid-19 vaccination as an effort by the government to suppress the spread of the Covid-19 virus, the vaccination obligation is listed in Presidential Regulation Number 14 of 2021 as well as containing administrative and criminal sanctions for those who refuse vaccination, reasons for refusing vaccination due to fear of serious side effects that threaten life safety, so that it is not appropriate for criminal sanctions to be applied to people who refuse vaccines but obey health protocols. The purpose of this study is to determine the urgency of implementing criminal sanctions for those who refuse Covid-19 vaccination from the perspective of human rights as well as legal consequences and legal protection for recipients and refusals of Covid-19 vaccination in Indonesia. This study uses a normative juridical approach to legislation and comparison and then analyzed qualitatively. As a result, it is concluded that the obligation to vaccinate is a form of human rights restriction in a health emergency, but the application of criminal sanctions for vaccination refusals is full of difficulties and complications, although it can function as an effort to comply with the community, and as a result, vaccine recipients get an international vaccination certificate. criminal law, while legal protections due to AEFI are regulated in-laws and regulations. In addition, victims can apply for other legal steps in civil, criminal, or through consumer protection. Therefore, a Perpu vaccination is needed to ensure legal certainty through a social approach and restorative justice in the success of vaccination.Pelaksanaan vaksinasi Covid-19 sebagai upaya pemerintah untuk menekan penyebaran virus Covid-19 maka kewajiban vaksinasi tercantum pada Perpres Nomor 14 Tahun 2021 sekaligus memuat sanksi administratif dan pidana bagi yang menolak vaksinasi, alasan penolakan vaksinasi karena ketakutan terhadap efek samping serius yang mengacam keselamatan jiwa, sehingga tidak tepat sanksi pidana diterapkan kepada orang yang menolak vaksin namun taat menerapkan protokol kesehatan. Tujuan penelitian ini untuk mengetahui urgensi penerapan sanksi pidana bagi yang menolak vaksinasi Covid-19 ditinjau dari perspektif HAM serta akibat hukum dan perlindungan hukum bagi penerima maupun penolak vaksinasi Covid-19 di Indonesia. Penelitian ini menggunakan yuridis normatif dengan pendekatan perundang-undangan dan perbandingan lalu dianalisis secara kualitatif. Sehingga dihasilkan bahwa kewajiban vaksinasi merupakan bentuk pembatasan HAM pada keadaan darurat kesehatan namun penerapan sanksi pidana bagi penolak vaksinasi sarat akan kesulitan dan kerumitan walaupun dapat berfungsi sebagai upaya kepatuhan masyarakat, dan akibat hukumnya penerima vaksin mendapatkan sertifikat vaksinasi internasional, bagi penolak vaksin dikenakan sanksi administratif dan pidana, sedangkan perlindungan hukum akibat KIPI diatur dalam peraturan perundang-undangan selain itu korban dapat mengajukan langkah hukum lain secara perdata, pidana, atau melalui perlindungan konsumen. Maka diperlukan Perpu vaksinasi untuk menjamin kepastian hukum melalui pendekatan sosial dan restorative justice dalam mensukseskan vaksinasi.